2011
DOI: 10.1080/15299716.2011.545285
|View full text |Cite
|
Sign up to set email alerts
|

An Empirical Study into the Relationship between Bisexual Identity Congruence, Internalized Biphobia and Infidelity among Bisexual Women

Abstract: This study examined the relationship between bisexual identity congruence, internalized biphobia and infidelity among women who are attracted to men and women. Bisexual identity congruence was measured by an adapted Klein Sexual Orientation Grid, internalized biphobia was measured by an adapted version of the Lesbian Internalized Homophobia Scale and infidelity was measured by a questionnaire created by the authors measuring sexual and emotional infidelity in relationships with men and with women. Results show… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
14
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(15 citation statements)
references
References 33 publications
1
14
0
Order By: Relevance
“…Past research has found negative consequences of internalized bi-negativity (e.g. Ochs, 1996) and a significant relationship between bisexual identity congruence and internalized bi-negativity (Hoang et al., 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Past research has found negative consequences of internalized bi-negativity (e.g. Ochs, 1996) and a significant relationship between bisexual identity congruence and internalized bi-negativity (Hoang et al., 2011).…”
Section: Discussionmentioning
confidence: 99%
“…This task was informed by an emerging literature on social identity complexity that has concerned itself with the relationships between MGMs, and the degree to which these may be (dys)functional (e.g., Benet?Martínez, & Haritatos, ; Ramarajan, ). Researchers have also argued for the importance of identity congruence (Hoang, Holloway, & Mendoza, ) or identity integration (Amiot, de la Sablonnière, Terry, & Smith, ), which we consider conceptually similar to group compatibility (Iyer, Jetten, Tsivrikos, Postmes, & Haslam, ). This procedure provided a basis for the last of the four core SIM constructs – Group Compatibility – which was calculated as the proportion of links between groups that was rated as ‘very easy’ (to be a member of two groups).…”
Section: Introductionmentioning
confidence: 92%
“…Thus, women who have male and female partners (sequentially or simultaneously) and adjust their identity according to the gender of each partner risk destabilizing their social network. Accordingly, switching from a lesbian identity to a bisexual identity may be a particularly threatening prospect, as there are few cohesive communities for bisexually-identified women (Bradford, 2004;Hoang, Holloway, & Mendoza, 2011;Mulick & Wright, 2002). As a result, women within lesbian communities who have occasional male sexual partners may fear the ghettoization (e.g., expulsion from the lesbian community) that could result from a modification of their sexual identity to one that matches their sexual behavior (e.g., bisexual) (Rust, 1992).…”
mentioning
confidence: 93%